2016
DOI: 10.1177/0300060516664636
|View full text |Cite
|
Sign up to set email alerts
|

The adaption and evaluation of a Latvian version of the National Institutes of Health Stroke Scale

Abstract: ObjectivesTo determine the validity and reliability of a Latvian version of the National Institutes of Health Stroke Scale (LV-NIHSS) for evaluating Latvian stroke patients.MethodsThe adaption of the LV-NIHSS followed standard methods used for the adaption and validation of clinical assessment tools. The scale validity was tested by comparison with the Glasgow Coma Scale (GCS) and the modified Rankin scale (mRs). The reliability of the LV-NIHSS was evaluated by intra-rater and inter-rater agreement using intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our findings are consistent with those of other studies in this topic; however, we noted higher individual item agreement values than those reported by most other investigators. Only one report by Jurjans et al [ 26 ] found that all the items of a Latvian validated tool achieved excellent ICC (> 0.95) in both inter-rater and intra-rater assessments. The authors of validation reports of other scales found moderate, and sometimes, even poor agreement between the selected items [ 9 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of other studies in this topic; however, we noted higher individual item agreement values than those reported by most other investigators. Only one report by Jurjans et al [ 26 ] found that all the items of a Latvian validated tool achieved excellent ICC (> 0.95) in both inter-rater and intra-rater assessments. The authors of validation reports of other scales found moderate, and sometimes, even poor agreement between the selected items [ 9 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used the modified Rankin scale (mRS) and the Latvian version of the National Institute of Health Stroke Scale (LV-NIHSS) to measure the functional and neurological outcomes of patients [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…We collected the patients’ clinical data using the local stroke registry, including patients’ demographic data, vascular risk factors, and functional neurological evaluation results. The Latvian version of the National Institutes of Health Stroke Scale (NIHSS-LV) was used to evaluate patients’ neurological outcomes at discharge, and the modified Rankin scale (mRS) was used for assessing the functional outcome [ 10 , 11 , 12 ]. The trial of ORG 10172 in acute stroke treatment (TOAST) classification was used for the determination of stroke etiology [ 13 ].…”
Section: Methodsmentioning
confidence: 99%